2017
DOI: 10.1080/09546634.2017.1395796
|View full text |Cite
|
Sign up to set email alerts
|

Review of IL-17 inhibitors for psoriasis

Abstract: The clinical improvement among psoriasis patients on IL-17 inhibitors is similar or superior to the improvement seen with commercially produced biologic agents available accompanied by a favorable short-term safety profile. The results of the phase III trials indicate that IL-17 inhibitors are effective therapeutic options for psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Preclinical studies have provided promising results in murine models of neutrophilic airway diseases by using IL-17A-or IL-17RA-neutralizing antibodies, indicating that IL-17A signaling inhibition could be a novel therapeutic approach for treatment of these steroid-resistant diseases (3, 6-10). Neutralizing monoclonal antibodies (mAbs) (against IL-17A and IL-17RA) have been developed as candidate drugs targeting IL-17A-dependent pathogenesis (39)(40)(41)(42). However, given the considerable cost of antibody production and limited administration (only through the i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have provided promising results in murine models of neutrophilic airway diseases by using IL-17A-or IL-17RA-neutralizing antibodies, indicating that IL-17A signaling inhibition could be a novel therapeutic approach for treatment of these steroid-resistant diseases (3, 6-10). Neutralizing monoclonal antibodies (mAbs) (against IL-17A and IL-17RA) have been developed as candidate drugs targeting IL-17A-dependent pathogenesis (39)(40)(41)(42). However, given the considerable cost of antibody production and limited administration (only through the i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in skin immunopathology seen herein are consistent with the well-described ability of the gut microbiome to influence immunity in the skin via the so-called gut-skin-axis (158). A role for IL-17 in psoriasis has been established (159) and several studies in humans have also found an association between gut microbiota and Th17 responses (160, 161). Promotion of systemic Th17/IL-17 responses by acetate was also reported in another infectious disease setting where mice were infected orally with the gram-negative enteric bacteria Citrobacter rodentium (19).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative reviews on anti-IL-17 drugs reported that all three drugs were well-tolerated in patients with moderate-to-severe psoriasis; however, adverse effects, such as respiratory tract infections, were reported more frequently for ixekizumab, and it was withdrawn in some cases due to its toxicity [204,205]. A meta-analysis on efficacy of anti-IL-17 drugs on rheumatoid arthritis showed that secukinumab and ixekizumab were more effective compared to placebo; however, an increased risk of infection in the test group has also been reported [206].…”
Section: Th17/il-17 As Targets In the Management Of Imids And Its mentioning
confidence: 99%